1998
DOI: 10.1046/j.1365-4362.1998.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of onychomycosis in southern Greece

Abstract: Comparison of the results of epidemiological studies of onychomycosis worldwide show great differences, not only between different countries and different climate zones, but also between studies performed in the same country. In our opinion such epidemiological studies should be performed in every country in order to determine the major fungal species responsible; such information is extremely useful in the treatment of nail onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 14 publications
9
26
1
Order By: Relevance
“…In our own unpublished data, the incidence of onychomycosis in 103 patients with nail psoriasis (Fig. ) has been found to be 11.67% and this number does not differ in a statistically significant manner from the incidence of onychomycosis that was found in Southern Greece published by one of the authors of this study …”
Section: Should We Distinguish the Two Diseases Or Should We Prove Thsupporting
confidence: 50%
“…In our own unpublished data, the incidence of onychomycosis in 103 patients with nail psoriasis (Fig. ) has been found to be 11.67% and this number does not differ in a statistically significant manner from the incidence of onychomycosis that was found in Southern Greece published by one of the authors of this study …”
Section: Should We Distinguish the Two Diseases Or Should We Prove Thsupporting
confidence: 50%
“…The prevalence of these pathogens, however, varies according to geography, climate, and patterns of population migration, and it may differ among regions with similar environmental conditions. The few onychomycosis studies that have been carried out for the Balkan region (27,39,41,48), where the patient population of the present study originated, have shown that the two dermatophyte species predominate, making up 55 to 70% of isolates from nails, while molds and yeasts are less common, growing from 10 to 27% of specimens (but not always rigorously implicated as causal). Variation among countries is evident.…”
Section: Discussionmentioning
confidence: 71%
“…Secondly, because of limitations in our laboratory facilities, the diagnosis of onychomycosis was limited to histopathologic examination (KOH stain) of the toenails, with no fungus culture. Although Rigopoulos et al 32 . reported that toenail onychomycosis was caused most frequently by dermatophytes (71%), a previous study in Taiwan reported that 60.5% of onychomycosis was caused by dermatophytes, 31.5% by Candida , and 8% by nondermatophyte molds 33 .…”
Section: Discussionmentioning
confidence: 93%